ANALISIS KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH AKUISISI PERIODE 2011 - 2013 - RIZKY, ARDHIANSYAH; NYOMAN ALIT TRIANI, NI (Jurnal Akuntansi AKUNESA, 2018)
Acquisition is a merger of a business by acquisition of shares or assets of another company for the purpose of adding core capital. One of the fundamental motives of acquisition is an economic motive.This research was aimed to analyze the differences between financial performance before and after the acquisition. The financial performance used in this research are profitability, liquidity, activity, market value and leverage. The research set an object on a companies which listed in Indonesia Stock Exchange at 2011-2013. The period before acquisition is 2011-2013. As the period after acquisition is 2014-2016. The research data used were obtained from company?s annual audit report (IDX) and the company website. This research used secondary data with quantitative approach. The analysis method that used on thus research was different test method. There are two different test used in this research, two paired t-test and wilcoxon sign rank test. The result shows that liquidity and market value doesn?t significantly differences before and after the acquisition. It shows that liquidity and market value is not of the reasons which considered by the company in determining the acquisition action. Whereas profitability, activity, and leverage significantly differences before and after the acquisition.